2001
DOI: 10.1002/1529-0131(200106)44:6<1281::aid-art220>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Specific overexpression of rheumatoid arthritis-associated HLA-DR alleles and presentation of low-affinity peptides

Abstract: Objective To compare levels of HLA–DR expression in rheumatoid arthritis (RA) patients and healthy controls for whom an ordered expression according to the DR alleles is demonstrated and to test the functional consequences of this expression on peptide presentation. Methods Using monoclonal antibodies that recognize different DRB1 alleles, DR molecules were quantitated at the surface of the peripheral blood B cells of 23 RA patients and 17 healthy subjects. The functional consequences of the level of DR surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Differential expression of HLA-DRB alleles has been reported in various cell types and diseases [32,33]. Particularly relevant is a report by Kerlan-Candon et al [20] that showed SE-bearing alleles (DRB1*04 and B1*01) were more highly expressed in B cells from RA patients than in those from healthy individuals. Although a similar trend was seen in this study, a larger number of samples would be required to determine differences in SE ϩ allele expression between RA and non-RA cFLS.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Differential expression of HLA-DRB alleles has been reported in various cell types and diseases [32,33]. Particularly relevant is a report by Kerlan-Candon et al [20] that showed SE-bearing alleles (DRB1*04 and B1*01) were more highly expressed in B cells from RA patients than in those from healthy individuals. Although a similar trend was seen in this study, a larger number of samples would be required to determine differences in SE ϩ allele expression between RA and non-RA cFLS.…”
Section: Discussionmentioning
confidence: 98%
“…Differences in antigen-presenting capabilities of APC from RA patients have been reported, including reduced HLA-DM expression in B cells [19] and increased expression of RA-associated alleles [20]. Although some studies have examined the ability of HLA class IIpositive fibroblasts to activate T cells [21], little is known regarding the presence or function of various components of the class II pathway in cFLS.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, HLA-DR can provide a first signal to the development of an effective immune response by the specific peptide-MHC antigen complex formation. In the context of RA, the elevated levels of HLA-DR4, DR1, and DR10 gene, which promote Th1 predominant advantage within RA immune imbalance, have previously been described for various cell types [41][42][43][44][45]. In addition to a first signal, the T and B lymphocytes require the other nonspecific signal, which is provided by the interaction between co-stimulatory molecules expressed on the membrane of APC and the lymphocytes, to become fully activated.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased and increased expression of ARPI and TNFAIP3, respectively, might be a feedback system suppressing further inflammation. HLA‐DRB1, a genotype known to be a risk factor of RA [29], was increased in RA [30]. Its expression might relate to autoantigen presentation.…”
Section: Discussionmentioning
confidence: 99%